A study on side effects of antibiotics used in the treatment of patients with head trauma and legal responsibility of clinicians in terms of the right to health (Annals of Medical Research, 2021)
Aim: Patients with head trauma are routinely, and commonly treated with prophylactic antibiotics, which may also be used for the treatment of infection that may be developed during hospital stay. The relevant antibiotic may, however, some side effects and adverse event. The present study aimed to investigate whether the side effects and adverse events of the prophylactic antibiotics were considered as a complication or medical negligence.Material and Methods: Descriptive statistics were used for the evaluation of the data.Results: No studies were found in the literature. Ceftriaxone, ampicillin-sulbactam, and cefazolin sodium were preferred for antibiotherapy. Meropenem or vancomycin was solely administered to patients when observed active pathogens in culture-antibiogram. Clinicians should be cautioned the potential side effects and adverse events of some drugs frequently used in clinics. Conclusion: Otherwise, they may legally be held liable for medical negligence.Keywords: Adverse effect; head trauma; human rights; malpractice; negligence; rational antibiotic use; right to health; side effect; professional liability.
Keywords: Adverse effect; head trauma; human rights; malpractice; negligence; rational antibiotic use; right to health; side effect; professional liability.